Analysis of the Motives for the Ban on Exports of Indonesian Palm Oil Products by the European Union in 2017 - Kurnianingsih, Eka; Rachmawati, Tety; Karisma, Gita (Global Local Interactions: Journal of International Relations, 2024)
The European Union (EU) adopted a Resolution on Palm Oil and Deforestation on Rainforest that contains a ban on Indonesian palm oil (CPO) exports. The ban on Indonesian CPO exports was carried out by the EU on the accusation that Indonesia's CPO production causes deforestation. Thus, the resolution became a CPO trade dispute between Indonesia and the EU. This research aims to find the EU's motives in the Indonesian CPO export ban policy. The research method used is descriptive qualitative method using secondary data obtained from the Central Statistics Agency (BPS), Index Mundi, International Trade Center (ITC), Observatory of Economic Complexity (OEC). The results showed that the EU has a motive (national interest) which is to develop the domestic vegetable oil industry of rapeseed oil (RSO), sunflower oil (SFO), and soybeen oil (SBO) in the Indonesian CPO export ban policy. The resolution issued by the EU against the Indonesian palm oil industry is a form of protection of these domestic vegetable oils.